Cleaning up : how hospital outsourcing is hurting workers and endangering patients - Zuberi, Dan (Culture and politics of health care work., 2013)
"To cut costs and maximize profits, hospitals in the United States and many other countries are outsourcing such tasks as cleaning and food preparation to private contractors. In Cleaning Up, the first book to examine this transformation in the healthcare industry, Dan Zuberi looks at the consequences of outsourcing from two perspectives: its impact on patient safety and its role in increasing socioeconomic inequality. Drawing on years of field research in Vancouver, Canada as well as data from hospitals in the U.S. and Europe, he argues that outsourcing has been disastrous for the cleanliness of hospitals--leading to an increased risk of hospital-acquired infections, a leading cause of severe illness and death--as well as for the effective delivery of other hospital services and the workers themselves. Zuberi's interviews with the low-wage workers who keep hospitals running uncover claims of exposure to near-constant risk of injury and illness. Many report serious concerns about the quality of the work due to understaffing, high turnover, poor training and experience, inadequate cleaning supplies, and on-the-job injuries. Zuberi also presents policy recommendations for improving patient safety by reducing the risk of hospital-acquired infection and ameliorating the work conditions and quality of life of hospital support workers. He makes the case that hospital outsourcing exemplifies the trend towards "low-road" service-sector jobs that threatens to undermine society's social health, as well as the physical health and well-being of patients in health care settings globally"--